Language Proficiency, Information Behavior, and Reliance on Official Information among BIPA Learners - Joseph Saera, Idda; Gani, Fuad; Iswary Lawanda, Ike (International Journal of Language Teaching and Education, 2026)
This study explored the relationship between Indonesian language proficiency and information behavior patterns, specifically reliance on official information sources, among BIPA learners in Indonesia. Using an explanatory quantitative design, data were collected through an online survey from 92 respondents (prior and currently enrolled in BIPA programs from multiple universities in Indonesia). The instrument captured language proficiency, patterns of electronic resources use, perceived accessibility, and reliance on official information channels. Data were analyzed using descriptive statistics, reliability testing, correlation analysis, and multiple regression using IBM SPSS Statistics 31. The findings indicate that while language proficiency is positively associated in reliance, it does not significantly predict reliance when controlling for passive accessibility. Instead, passive accessibility emerges as the strongest predictor. The research findings show that BIPA learners interact with the digital information environment, relying moderately on official information channels. This study emphasizes the importance of usability and clarity in shaping information behavior in multilingual digital settings. This study contributes to information behavior research by providing empirical insights into how non-native speakers engage with official information in multilingual digital environments. This study provides practical tools and insights for policymakers, educators, and information providers to enhance the accessibility and efficiency of government information systems for international users in Indonesia.